Successful rechallenge with avelumab in a patient with advanced Merkel cell carcinoma who presented pembrolizumab‐induced myositis - Clémence Bertold; Laura Troin; Madleen Chassang; Thierry Passeron; Jérôme Doyen; Henri Montaudié; Alexandra Picard‐Gauci (Wiley, 2023)
Abstract Merkel cell carcinoma (MCC) is a rare and aggressive neuroendocrine skin cancer, associated with high mortality. Immune checkpoint inhibitors (ICIs) have demonstrated long‐lasting efficiency for treating advanced MCC. Despite a good safety profile, ICI remain associated with non‐negligible risk of immune‐related adverse events (irAEs), which may require treatment discontinuation if they are severe. We report the case of a long‐lasting complete response to Avelumab after rechallenge in a patient with a metastatic MCC who became resistant to this anti‐Programmed cell Death Ligand 1 (anti‐PD‐L1) treatment and who presented severe neuromuscular toxicity during anti‐PD‐1 treatment with Pembrolizumab, without recurrence of the irAE. The potential specificity of therapeutic properties and irAEs of each ICI supports a personalized management of antitumoral immunogenic response and its adverse effects.